Red-light photons on skin cells and the mechanism of photobiomodulation - Herrera, Manuel Alejandro; Ribas, Arthur Pereira; da Costa, Paulo Eduardo; Baptista, Mauricio S. (Frontiers in Photonics, 2024)
Red light (600-700 nm, ~2.1-1.8 eV) consists of a low-energy radiation with a high capacity to penetrate the skin and to induce stimulatory effects. These characteristics make this wavelength range very promising for light-based therapies. Aiming to discuss the mechanisms of action of photobiomodulation, we start by providing a broad perspective of the skin and of its interaction with light, focusing on the endogenous photosensitizers, on the formation of excited states and reactive oxidants, and on the activation of signaling effectors. The peculiar aspect of the photons in the red spectral range is that they are much less absorbed by the endogenous photosensitizers and consequently generate a lot fewer reactive oxidants (when compared with the other ranges of visible light), allowing the skin to mainly experience the consequences of several signaling pathways that are activated during the skin interaction with red-light photons. Indeed, the effects of red light in epithelial cells involve the control of metabolic responses, the modulation of several key genes and transcriptions factors, as well as the regulation of the intracellular nitric oxide stocks. In this article, we discuss how red light interacts with all these variables and end up causing a vigorous tissue activation. We also analyzed the effect of red-light photons on the nitric oxide homeostasis, with implications for the phototherapy of psoriasis. It is likely that several of the observations and mechanisms described for the interactions of red-light photons may also be occurring during and after the interaction with other photons with similar energy.